Oxytocin does not impact forced-choice recognition memory in an experimental trauma film paradigm with healthy women - Maslahati, Tolou; Glogau, Franziska; Galve Gómez, Milagros; Buchholz, Katharina; Dormann, Lisa; Wingenfeld, Katja; Otte, Christian; Schultebraucks, Katharina; Roepke, Stefan (Frontiers in Psychiatry, 2025)
IntroductionTraumatic experiences are thought to alter memory acquisition and consolidation. Cognitive models of PTSD suggest that voluntary and involuntary memories after trauma can be independently addressed through interventions. The administration of oxytocin before exposure to a trauma film led to more intrusive (involuntary) memories than placebo. The effect of oxytocin on voluntary memory of the traumatic film, however, remains unclear. The current study aimed to assess whether intranasal oxytocin administration facilitates forced-choice recognition memory after a trauma film paradigm.Material & methodsWe performed a pooled analysis of two randomized, double-blind, placebo-controlled studies (N = 437) to assess the impact of intranasal oxytocin administration on declarative memory. Participants received 24 I.U. of oxytocin, either 40 minutes before a trauma film paradigm or immediately afterward. We applied a forced-choice recognition task seven days after the trauma film paradigm. The task comprised pre-, peri, and post-trauma film scene details.ResultsThe administration of oxytocin did not affect recognition performance for any film scene (F(2, 401) = .49, p = .61). Participants remembered significantly more peri-traumatic film details compared to pre- and post-trauma details (F(1.72, 802) = 103.38, p <.001).DiscussionAlthough the exogenous oxytocin administration before a trauma film has been shown to influence the acquisition of intrusive memories, it does not seem to affect the recognition memory of trauma film details. That aligns with cognitive models of PTSD, suggesting that voluntary and involuntary memory after trauma can be independently addressed through experimental interventions.